An epoxy resin composition and use thereof

CN117343482BActive Publication Date: 2026-10-30GUANGDONG SHENGYI SCI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311453184.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-03
Publication Date
2026-10-30
Estimated Expiration
2043-11-03

AI Technical Summary

Technical Problem

[0004]业界有尝试用偶联剂表面处理氮化硼,以提高其与树脂的结合力,但因为氮化硼的边缘含有的羟基很少,难以直接在其表面上接枝偶联剂

Benefits of technology

本发明通过使用强碱溶液对氮化硼表面进行侵蚀预处理,得到表面羟基化的氮化硼,然后使用复配的偶联剂做表面处理,得到改性后的氮化硼,将改性后的氮化硼添加到环氧树脂体系中,得到环氧树脂组合物,使用该环氧树脂组合物所制备的覆铜板,其铜箔剥离强度明显提高、热导率不会降低、同时也提高了板材的耐电压能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application provides an epoxy resin composition and application thereof, the epoxy resin composition comprises the following components by weight: epoxy resin 23-31 parts, curing agent 9-20 parts and modified boron nitride 40-55 parts; the modified boron nitride is obtained by using a strong alkali solution to erode the surface of boron nitride for pretreatment, obtaining boron nitride with surface hydroxylation, then using a compounded coupling agent for surface treatment to obtain modified boron nitride, adding the modified boron nitride into the epoxy resin system to obtain the epoxy resin composition, the copper clad plate prepared by using the epoxy resin composition has obviously improved copper foil peeling strength, the thermal conductivity does not decrease, and the voltage resistance of the plate is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of copper clad laminate technology and relates to an epoxy resin composition and its application. Background Technology

[0002] As electronic products become lighter, thinner, shorter, and smaller, the requirements for heat dissipation in electronic devices are becoming increasingly stringent. Boron nitride has a low coefficient of thermal expansion, a low dielectric constant, and high thermal conductivity, and its application in copper-clad laminates (CCLs) will become increasingly widespread. However, because boron nitride has a smooth, sheet-like structure, its direct application in CCLs will reduce the copper foil peel strength of the board.

[0003] In this field, the use of boron nitride significantly reduces the copper foil peel strength of copper-clad laminates. In the copper-clad laminate industry, the bonding strength between the resin layer and the copper foil is a very important performance indicator.

[0004] The industry has attempted to surface-treat boron nitride with coupling agents to improve its adhesion to resins. However, because boron nitride contains very few hydroxyl groups at its edges, it is difficult to directly graft coupling agents onto its surface. Therefore, a new method is needed to graft coupling agents onto the surface of boron nitride, in order to ensure both the adhesion between the resin layer and the copper foil, and the overall performance of the copper-clad laminate. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide an epoxy resin composition and its application.

[0006] To achieve this objective, the present invention adopts the following technical solution: On one hand, the present invention provides an epoxy resin composition comprising the following components in parts by weight: 23-31 parts epoxy resin, 9-20 parts curing agent, and 40-55 parts modified boron nitride. The modification method for the modified boron nitride includes the following steps: (1) Boron nitride was pretreated with a strong alkaline solution to obtain surface-pretreated boron nitride; (2) The boron nitride obtained in step (1) is subjected to surface treatment after being combined with coupling agent A and coupling agent B. Coupling agent A is 3-isocyanate propyltriethoxysilane, and coupling agent B is selected from any one or a combination of at least two of N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, N-phenyl-8-aminooctyl-trimethoxysilane, 7-octenaltrimethoxysilane, 8-glycidyl etheroxyoctyltrimethoxysilane, octyltriethoxysilane or 8-methacryloyloxyoctyltrimethoxysilane.

[0007] In this invention, by using a compound of two coupling agents to modify boron nitride, the laminate prepared using modified boron nitride exhibits higher copper foil peel strength, without decreasing thermal conductivity, and higher voltage withstand capability compared to laminate prepared using unmodified boron nitride. The inventors hypothesize that the relevant mechanism is as follows: in the compounded coupling agents, the propyl isocyanate group in coupling agent A has strong reactivity and reacts more readily with the hydroxyl groups on the surface of the boron nitride filler. The long-chain structure in coupling agent B increases the degrees of freedom at both ends, making one end easily react with coupling agent A on the boron nitride surface and the other end easily react with the host resin. The modified boron nitride of this invention has good affinity with the host resin, and boron nitride is less prone to self- and interfacial damage, resulting in a laminate with excellent copper foil peel strength and high voltage withstand capability.

[0008] Preferably, the strongly alkaline solution is an aqueous solution of sodium hydroxide and / or potassium hydroxide. For example, sodium hydroxide and / or potassium hydroxide can be dissolved in purified water by stirring to obtain OH. - A strongly alkaline solution with a concentration of 0.5-10 mol / L, for example, a concentration of 0.5 mol / L, 1 mol / L, 2 mol / L, 5 mol / L, 8 mol / L or 10 mol / L.

[0009] Preferably, the pretreatment temperature is 100-125℃ (e.g., 102℃, 105℃, 108℃, 110℃, 112℃, 115℃, 118℃, 120℃ or 122℃), and the pretreatment time is 1-24 hours (e.g., 1 hour, 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours or 22 hours).

[0010] After pretreatment, boron nitride can be further subjected to filtration, washing, drying, and other operations, which will not be elaborated here.

[0011] Preferably, the boron nitride obtained in step (1) is surface-treated using a solution of coupling agent A and coupling agent B. For example, coupling agent A and coupling agent B can be dissolved in a solvent to obtain a solution. The solvent is not particularly limited; specific examples include alcohols such as methanol, ethanol, and butanol; ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol-methyl ether, carbitol, and butyl carbitol; ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and mesitylene; esters such as ethoxyethyl acetate and ethyl acetate; and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. The solvents mentioned above can be used alone or in combination of two or more. It is preferred that aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene be used in combination with ketone fluxes such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0012] Of course, the boron nitride obtained in step (1) can also be surface-treated using the dry spraying method commonly used in this field, which will not be elaborated here.

[0013] Preferably, the surface treatment temperature is 100-125℃ (e.g., 102℃, 105℃, 108℃, 110℃, 112℃, 115℃, 118℃, 120℃ or 122℃), and the surface treatment time is 1-24 hours (e.g., 1 hour, 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours or 22 hours).

[0014] In this invention, after the surface treatment, boron nitride can be further subjected to operations such as filtration, washing, and drying, which will not be elaborated here.

[0015] In this invention, the total amount of coupling agent A and coupling agent B is 2-5% of the weight of boron nitride, for example 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0016] In this invention, based on the total weight of coupling agent A and coupling agent B as 100%, the proportion of coupling agent A is 50-90% (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%), and the proportion of coupling agent B is 10-50% (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).

[0017] Preferably, the average particle size D50 of the boron nitride is 2-30 μm, for example, 3 μm, 5 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, or 28 μm. This invention relates to measuring the average particle size D50 using laser diffraction, with the Malvern laser particle size analyzer, model MS3000, as the testing instrument.

[0018] In this invention, the epoxy resin includes any one or a combination of at least two of the following: bisphenol A type epoxy resin, bisphenol F type epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, phenolic epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, naphthalene-containing epoxy resin, or alicyclic epoxy resin.

[0019] In this invention, the curing agent includes any one or a combination of at least two of the following: phenolic resin curing agents, reactive ester curing agents, amine curing agents, acid anhydride curing agents, carboxylic acid curing agents, cyanate ester curing agents, benzoxazine curing agents, or maleimide curing agents.

[0020] Preferably, the phenolic resin includes any one or a combination of at least two of bisphenol A type phenolic resin, phenolic resin, biphenyl type phenolic resin, dicyclopentadiene type phenolic resin, or naphthol-containing phenolic resin.

[0021] In this invention, the epoxy resin content in the epoxy resin composition can be 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, 30 parts by weight, or 31 parts by weight; the curing agent content can be 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight; and the modified boron nitride content can be 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, or 55 parts by weight.

[0022] Preferably, the epoxy resin composition further comprises 5-20 parts of metal oxide and / or non-metal oxide fillers, such as 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight or 20 parts by weight.

[0023] Preferably, the metal oxide and / or non-metal oxide filler is selected from any one or a combination of at least two of alumina, silicon oxide, beryllium oxide, magnesium oxide or zinc oxide.

[0024] Preferably, the epoxy resin composition further includes 0.01-3 parts of a curing accelerator, such as 0.02 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.5 parts by weight, 0.8 parts by weight, 1 part by weight, 2 parts by weight or 3 parts by weight.

[0025] Preferably, the curing accelerator includes any one or a combination of at least two of imidazole accelerators and their derivatives, Lewis acids, triphenylphosphine, or pyridine accelerators.

[0026] On the other hand, the present invention provides a resin film, wherein the resin film is prepared from an epoxy resin composition as described above.

[0027] Preferably, the resin film is obtained by coating the epoxy resin composition as described above onto a release material and then drying and / or semi-curing it.

[0028] Preferably, the thickness of the resin film is 5-300 μm, such as 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, more preferably 10-200 μm, and even more preferably 20-100 μm.

[0029] On the other hand, the present invention provides a resin-coated copper foil, the resin-coated copper foil comprising a copper foil layer and a resin layer, wherein the material of the resin layer comprises the epoxy resin composition described above.

[0030] Preferably, the resin layer is an epoxy resin composition as described above that is applied to the copper foil after coating and drying.

[0031] Preferably, the thickness of the resin layer is 5-300 μm, such as 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, more preferably 10-200 μm, and even more preferably 20-100 μm.

[0032] Preferably, the thickness of the copper foil is 1-105 μm, such as 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm or 105 μm, more preferably 3-35 μm, and even more preferably 5-18 μm.

[0033] Preferably, the resin-coated copper foil further includes a protective film covering the resin layer.

[0034] On the other hand, the present invention provides a prepreg, the prepreg comprising a substrate and an epoxy resin composition as described above that is attached to the substrate after impregnation and drying.

[0035] The semi-cured sheet described in this invention can also be referred to as a prepreg or adhesive sheet, and the substrate described in this invention can also be referred to as a reinforcing material.

[0036] Preferably, the substrate is E-glass fiber cloth, NE-glass fiber cloth, quartz glass fiber cloth, or aromatic amine cloth, etc.

[0037] On the other hand, the present invention provides a laminate comprising at least one prepreg sheet as described above.

[0038] On the other hand, the present invention provides a metal foil laminate, the metal foil laminate comprising one or at least two stacked prepreg sheets as described above, and metal foil located on one or both sides of the stacked prepreg sheets.

[0039] On the other hand, the present invention provides a circuit board comprising one or at least two laminated prepreg sheets as described above.

[0040] Compared with the prior art, the present invention has the following beneficial effects: This invention pretreats the surface of boron nitride by etching with a strong alkaline solution to obtain surface-hydroxylated boron nitride. Then, a compounded coupling agent is used for surface treatment to obtain modified boron nitride. The modified boron nitride is added to an epoxy resin system to obtain an epoxy resin composition. The copper-clad laminate prepared using this epoxy resin composition has significantly improved copper foil peel strength, does not decrease thermal conductivity, and also improves the voltage resistance of the board. Detailed Implementation

[0041] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0042] The materials used in the following examples and comparative examples are as follows: Modified boron nitride 1: using OH -Boron nitride (D50 11 μm, SN30, purchased from Suzhou Jinyi) was pretreated with a 5 mol / L NaOH aqueous solution at 120 °C for 18 h, washed with water until neutral, and then dried to obtain surface-hydroxylated boron nitride. A solution was prepared by dissolving 3-isocyanate propyltriethoxysilane (Shin-Etsu Chemical, KBE-9007) and N-2-(aminoethyl)-8-aminooctyltrimethoxysilane (Shin-Etsu Chemical, KBM-6803) in toluene (KBE-9007:KBM-6803 weight ratio 70:30, total coupling agent amount 4% of boron nitride weight). The surface-hydroxylated boron nitride obtained from the aforementioned pretreatment was then surface-treated at 110 °C for 18 h, washed with toluene solvent, and dried to obtain modified boron nitride 1.

[0043] Modified boron nitride 2: using OH - Boron nitride (D50 3 μm, N23, Suzhou Jinyi) was pretreated with a 3 mol / L NaOH aqueous solution at 110 °C for 20 h, washed with water until neutral, and then dried to obtain surface-hydroxylated boron nitride. A solution was prepared by dissolving 3-isocyanate propyltriethoxysilane (Shin-Etsu Chemical, KBE-9007) and 8-glycidyl etheroxyoctyltrimethoxysilane (Shin-Etsu Chemical, KBM-4803) in toluene (KBE-9007:KBM-4803 weight ratio 50:50, total coupling agent amount 2% of boron nitride weight). The surface-hydroxylated boron nitride obtained from the aforementioned pretreatment was then surface-treated at 120 °C for 12 h, washed with toluene solvent, and dried to obtain modified boron nitride 2.

[0044] Modified boron nitride 3: using OH - Boron nitride (D50 23.3 μm, BN0251, Suzhou Jinyi) was pretreated with a 1 mol / L NaOH aqueous solution at 105 °C for 24 h, washed with water until neutral, and then dried to obtain surface-hydroxylated boron nitride. A solution was prepared by dissolving 3-isocyanate propyltriethoxysilane (Shin-Etsu Chemical, KBE-9007) and 8-methacryloyloxyoctyltrimethoxysilane (Shin-Etsu Chemical, KBM-5803) in toluene (KBE-9007:KBM-5803 weight ratio 90:10, total coupling agent amount 5% of boron nitride weight). The surface-hydroxylated boron nitride obtained from the aforementioned pretreatment was then surface-treated at 105 °C for 15 h, washed with toluene solvent, and dried to obtain modified boron nitride 3.

[0045] Boron nitride 4: D50 is 11μm, SN30, purchased from Suzhou Jinyi, without surface hydroxylation treatment or coupling agent surface treatment using strong alkaline solution.

[0046] Modified boron nitride 5: The only difference from modified boron nitride 1 is that N-2-(aminoethyl)-8-aminooctyltrimethoxysilane is replaced with an equal weight of 3-isocyanate propyltriethoxysilane. That is, only 3-isocyanate propyltriethoxysilane (Shin-Etsu Chemical, KBE-9007) is used for surface treatment in the coupling agent.

[0047] Modified boron nitride 6: The only difference from modified boron nitride 5 is that 3-isocyanate propyltriethoxysilane is replaced with an equal weight of 3-methacryloyloxypropyltrimethoxysilane. That is, only 3-methacryloyloxypropyltrimethoxysilane (Shin-Etsu Chemical, KBM-503) is used for surface treatment in the coupling agent.

[0048] Modified Boron Nitride 7: The only difference from Modified Boron Nitride 1 is that 3-isocyanate propyltriethoxysilane is replaced with an equal weight of 8-glycidyl etheroxy octyltrimethoxysilane. That is, the coupling agent is a combination of 8-glycidyl etheroxy octyltrimethoxysilane (Shin-Etsu Chemical, KBM-4803) and N-2-(aminoethyl)-8-aminooctyltrimethoxysilane (Shin-Etsu Chemical, KBM-6803) followed by surface treatment.

[0049] Alumina: BAK-0050, Shanghai Baitu High-Tech Materials Technology Co., Ltd.

[0050] Silica: 1028L, Jiangsu Lianrui.

[0051] Epoxy Resin 1: NC-3000H, Biphenylphenolic epoxy resin, Nippon Kayaku.

[0052] Epoxy Resin 2: EPR627M80, Bisphenol A phenolic epoxy resin, Momentive (USA).

[0053] Curing agent 1: 4,4-diaminodiphenyl sulfone (DDS), Atul, India.

[0054] Curing agent 2: Phenolic resin, SN-485, Nippon Steel Chemical Materials Co., Ltd.

[0055] Curing agent 3: Dicyclopentadiene type active ester, HPC-8000-65T, Japan DIC.

[0056] Curing accelerator 1: 2-phenylimidazole (2-PZ), BASF, Germany.

[0057] Curing accelerator 2: 4-Dimethylaminopyridine (DMAP), Guangrong Chemical.

[0058] Example The resin composition was prepared according to the components shown in Table 1. All weight parts mentioned in Table 1 refer to solid weight parts excluding solvent. The metal-based copper-clad laminate sample was then prepared according to the following method: The components of the formulation were mixed evenly in a solvent, controlling the solid content of the adhesive to 75%. The adhesive was then coated onto a release material (PET release film) and dried at 155℃ for 5 min to obtain a resin film with a semi-cured thermally conductive and insulating adhesive layer (100 μm thick). After removing the release film, the resin film was sandwiched between a surface-treated aluminum plate (1.0 mm thick) and a copper foil (35 μm thick) and vacuum-cured at 220℃ for 120 min, then pressed under a pressure of 2.5 MPa to obtain an aluminum-based copper-clad laminate. The performance testing methods for the aluminum-based copper-clad laminate are as follows: (1) Copper foil peel strength: The copper foil laminate sample was prepared and tested according to the method specified in IPC-TM-650 2.4.8; (2) Withstand voltage test: According to the method of T / CPCA 4105-2016, test the breakdown voltage of the thermally conductive insulation layer and take the average value of 5 points; (3) Thermal conductivity: The thermal conductivity of the metal-based copper-clad laminate was tested by preparing a sample of 25.4 mm × 25.4 mm according to the ASTM D5470 test method.

[0059] Table 1 As can be seen from Table 1, in Examples 1-3 of this application, the copper foil peel strength of the aluminum-based copper-clad laminate is 0.73-0.85 N / mm, the thermal conductivity is 1.80-2.00 W / m•K, and the withstand voltage is 17800-19000V. The copper-clad laminate obtained has high copper foil peel strength, high thermal conductivity, excellent voltage withstand capability, and good overall performance.

[0060] In Comparative Example 1, no strong alkaline solution was used for surface hydroxylation treatment and coupling agent surface treatment, resulting in a copper-clad laminate with a peel strength of only 0.45 N / mm and a withstand voltage of only 11000V. In Comparative Example 2, only 3-isocyanate propyltriethoxysilane was used for surface treatment, resulting in a copper foil peel strength of 0.65 N / mm and a withstand voltage of 16800V. In Comparative Example 3, only short-chain 3-methacryloyloxypropyltrimethoxysilane was used for surface treatment, resulting in a copper foil peel strength of 0.50 N / mm and a withstand voltage of 16500V. In Comparative Example 4, two long-chain coupling agents were used in combination, resulting in a copper foil peel strength of 0.68 N / mm and a withstand voltage of 17500V. In Comparative Example 5, the amount of modified boron nitride was too low, resulting in a copper-clad laminate with a thermal conductivity of only 0.85 W / m•K. The withstand voltage is 13700V; in Comparative Example 6, the amount of modified boron nitride is too high, and the peel strength of the copper-clad laminate is only 0.50 N / mm, and the withstand voltage is 14500V.

[0061] The applicant declares that the epoxy resin composition and its application of the present invention are illustrated through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An epoxy resin composition, characterized in that, The epoxy resin composition comprises the following components in parts by weight: 23-31 parts epoxy resin, 9-20 parts curing agent, and 40-55 parts modified boron nitride. The modification method for the modified boron nitride includes the following steps: (1) Boron nitride was pretreated with a strong alkaline solution to obtain surface-pretreated boron nitride; (2) The boron nitride obtained in step (1) is surface treated by using coupling agent A and coupling agent B in combination. Coupling agent A is 3-isocyanate propyltriethoxysilane, and coupling agent B is selected from any one or a combination of at least two of N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, 8-glycidyl etheroxyoctyltrimethoxysilane or 8-methacryloyloxyoctyltrimethoxysilane. The strongly alkaline solution is an aqueous solution of sodium hydroxide and / or potassium hydroxide; The pretreatment temperature is 100-125℃, and the pretreatment time is 1-24 hours; The total amount of coupling agent A and coupling agent B is 2-5% of the weight of boron nitride; Based on the total weight of coupling agent A and coupling agent B as 100%, the addition amount of coupling agent A is 50-90%, and the addition amount of coupling agent B is 10-50%. The average particle size D50 of the boron nitride is 2-30 μm.

2. The epoxy resin composition according to claim 1, characterized in that, The epoxy resin includes any one or a combination of at least two of the following: bisphenol A type epoxy resin, bisphenol F type epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, phenolic epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, naphthalene-containing epoxy resin, or alicyclic epoxy resin.

3. The epoxy resin composition according to claim 1, characterized in that, The curing agent includes any one or a combination of at least two of the following: phenolic resin curing agents, reactive ester curing agents, amine curing agents, acid anhydride curing agents, carboxylic acid curing agents, cyanate ester curing agents, benzoxazine curing agents, or maleimide curing agents.

4. The epoxy resin composition according to claim 3, characterized in that, The phenolic resin includes any one or a combination of at least two of the following: bisphenol A type phenolic resin, phenolic resin, biphenyl type phenolic resin, dicyclopentadiene type phenolic resin, or naphthol-containing phenolic resin.

5. The epoxy resin composition according to claim 1, characterized in that, The epoxy resin composition further includes 5-20 parts of metal oxide and / or non-metal oxide fillers.

6. The epoxy resin composition according to claim 5, characterized in that, The metal oxide and / or non-metal oxide filler is selected from any one or a combination of at least two of alumina, silicon oxide, beryllium oxide, magnesium oxide or zinc oxide.

7. The epoxy resin composition according to claim 1, characterized in that, The epoxy resin composition also includes 0.01-3 parts of a curing accelerator.

8. The epoxy resin composition according to claim 7, characterized in that, The curing accelerator includes any one or a combination of at least two of imidazole accelerators, Lewis acids, triphenylphosphine, or pyridine accelerators.

9. A resin film, characterized in that, The resin film is prepared from an epoxy resin composition as described in any one of claims 1-8.

10. The resin film according to claim 9, characterized in that, The resin film is obtained by coating an epoxy resin composition as described in any one of claims 1-8 onto a release material and then drying and / or semi-curing it.

11. The resin film according to claim 9, characterized in that, The thickness of the resin film is 5-300 μm.

12. The resin film according to claim 11, characterized in that, The thickness of the resin film is 10-200 μm.

13. The resin film according to claim 12, characterized in that, The thickness of the resin film is 20-100 μm.

14. A resin-coated copper foil, characterized in that, The resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the epoxy resin composition as described in any one of claims 1-8.

15. The resin-coated copper foil according to claim 14, characterized in that, The resin layer is an epoxy resin composition as described in any one of claims 1-8, which is applied to and dried onto a copper foil.

16. The resin-coated copper foil according to claim 14, characterized in that, The thickness of the resin layer is 5-300 μm.

17. The resin-coated copper foil according to claim 16, characterized in that, The thickness of the resin layer is 10-200 μm.

18. The resin-coated copper foil according to claim 17, characterized in that, The thickness of the resin layer is 20-100 μm.

19. The resin-coated copper foil according to claim 14, characterized in that, The thickness of the copper foil is 1-105 μm.

20. The resin-coated copper foil according to claim 14, characterized in that, The resin-coated copper foil also includes a protective film covering the resin layer.

21. A semi-cured sheet, characterized in that, The semi-cured sheet includes a substrate and an epoxy resin composition as described in any one of claims 1-8, which is attached to the substrate after impregnation and drying.

22. A laminate, characterized in that, The laminate includes at least one prepreg as described in claim 21.

23. A metal foil-coated laminate, characterized in that, The metal foil laminate includes one or at least two stacked prepreg sheets as described in claim 21, and metal foil located on one or both sides of the stacked prepreg sheets.

24. A circuit board, characterized in that, The circuit board includes one or at least two stacked prepreg sheets as described in claim 21.

Citation Information

Patent Citations

  • Method for producing organic-inorganic composite material including boron nitride particle aggregate

    JP2018053009A

  • Spherical boron nitride fine powder, method for manufacturing same and thermally conductive resin composition using same

    US20200048091A1